Description Of Student Satisfaction Of Level 3 Ners Producing During Online Learning In Santa Elisabeth Stikes Medan Year 2022 - Ice Septriani Saragih; Murni Sari Dewi Simanullang; Samafriati Sinurat; DAWINDA BR. MARBUN (Sean Institute, 2023)
Student satisfaction, namely, ease of accessibility, suitability of schedules, suitability of material, ease of understanding, discussion rooms, lecturers' abilities, media used in the online learning process and timeliness. Online learning is a learning system that is carried out non-face-to-face and carried out remotely using zoom, google classroom, edmodo, whatsapp which can help the teaching and learning process. The online learning media used in this research are google meet, google classroom, zoom, edmodo, whatsapp and others. The purpose of this study was to see a description of the satisfaction of level 3 Nursing Study Program students during online learning at STIKes Santa Elisabeth Medan in 2022. The research design used by the researcher was a descriptive study. The sampling technique is Total Sampling with 85 students as respondents. The results of the study showed that the gender of the majority of the respondents was female, namely 76 respondents (89.4%) and the majority of the respondents were from Batak Toba, namely 58 people (68.2%). With the level of student satisfaction the majority were in the moderate category as many as 44 people (51.8%) from 85 respondents. The results of this study can be used as a source of additional information and data for students and future researchers.